Adaptations in the transformation of cassava (Manihot esculenta Crantz; Euphorbiaceae) for consumption in the dietary management of diabetes: the case of Palikur, or Parikwene People, from French Guiana - Rapinski, Michael; Cuerrier, Alain; Davy, Damien (Frontiers in Nutrition, 2023)
In the French overseas department of French Guiana, in South America, nutrition therapy for the management of diabetes is based on French guidelines. However, this region is demographically diverse and includes several populations of Indigenous Peoples, Parikwene among others, also called Palikur. Due to socio-economical, cultural and geographical differences, along with distinctions in the local food system, dietary recommendations, which many consider in the context of post-colonial power dynamics, are not well suited to local populations. In the absence of suitable recommendations, it is hypothesized that local populations will adapt their dietary practices considering diabetes as an emerging health problem. Accordingly, Parikwene have adapted the transformation of cassava tubers (Manihot esculenta Crantz) for their consumption in the management of diabetes. Seventy-five interviews were conducted with community members and Elders, as well as healthcare professionals and administrators providing services to the Parikwene population of Macouria and Saint-Georges de l’Oyapock communes. The importance of cassava tubers as a staple and core food to the Parikwene food system was established by identifying it as a cultural keystone species. Narratives illustrated conflicting perceptions regarding the implication of cassava consumption in the development of diabetes. Adaptations to the operational sequence to the transformation of cassava tubers led to the production of distinct cassava roasted semolina (i.e., couac), based on organoleptic properties (i.e., sweet, and acidic couac). Preferences for the consumption of acidic couac were grounded in the Parikwene knowledge system, as well as attention to diabetes related symptoms and glucometer readings. These results provide important insights related to knowledge, attitudes, and practices in providing locally and culturally adapted approaches to providing dietary recommendations in the treatment of diabetes.